Urban workers, students, and guerrillas write history against the grain in the Brazilian society of 1968 - Bauer, Carlos (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article analyzes the presence of students, workers, and guerrillas in some political episodes documented since 1968 in Brazil. Based on a reflection about the close relationship of these social characters with the armed struggle and the importance of the political and organizational inheritance that fostered the social movements from the second half of the 1970s. The presence of these armed movements and their pedagogical nature, as an indivisible part of the history of social movements, allows us to understand them as agents of unexpected changes, contrary to the settlement of order and the mechanisms of domination, typical characteristics of a capitalist society. These movements dare to turn the world from head to toe and sow, in the fertile soil of history, the utopia of a society neither exploited nor with exploiters.